Research on the Evolution of Defects Initiation and the Diffusion of Dopant on the Si/SiO2 Interface - Yunqi Yang; Dongdong Chen; Di Li; Tianlong Zhao; Weida Zhang; Wen Qiao; Yingjie Liang; Yintang Yang (Advanced Materials Interfaces)
Abstract Si/SiO2 interfaces, important parts of Si‐based devices, significantly influence the performance of Si‐based devices. However, owing to the impact of the external environment, related defects are generated, and the dopant can diffuse and redistribute, causing a series of parasitic effects that reduce the lifespan of the devices. In this paper, recent investigations on the mechanisms of interface defect initiation and dopant diffusion are systematically reviewed. At the Si/SiO2 interface, Pb‐type center defects are identified, including Pb, Pb0, and Pb1 center defects. Near the interface, E’ center defects are identified, and H‐related defects are also formed. In addition, dopant ions are introduced in the Si/SiO2 interface to improve the conductivity. However, during the oxidation process, the dopant ions can diffuse and redistribute at the interface. Investigations of the dopant diffusion mechanism, modeling, and dopant pile‐up are reviewed in this paper. Comparisons and discussions of the initial mechanism of defects, structures of defects, and dopant diffusion mechanisms are presented to provide valuable guidance for improving the performance and extending the lifespan of Si/SiO2 interfaces. Finally, an outlook is presented, including improving the models of interface defects to better protect against local strains and multienvironment impacts, and developing 3D detection technology for dopants.